Kata Sapaan Kekerabatan yang Digunakan Masyarakat di Kecamatan Ranah Ampek Hulu Tapan Kabupaten Pesisir Selatan: Kajian Sosiolinguistik - Leni Syafyahya, Diny Aprilisyanda, Aslinda, (Puitika, 2023)
This study aims to describe the kinship greeting words used by the Minangkabau society in Ranah Ampek Hulu Tapan District. The theory used is the theory put forward by Koentjaraningrat about kinship terms of address. The methods used at the data provision stage are the listening method and the speaking method. In the data analysis stage, using the pragmatic equivalent method and the translational equivalent method. In the stage of presenting the results of data analysis using formal and informal methods. Based on the results of data analysis, the kinship terms of address used by the Minangkabau society in Ranah Ampek Hulu Tapan Distirct, Pesisir Selatan Regency are as follows: (1) The kinship terms of address used by the people in Ranah Ampek Hulu Tapan District are the core family, namelyÂ Bak, Ibung, Andak, Nah, Onen, Senu, Kaban.Â (2) The kinship terms of address used by the people in Ranah Ampek Hulu Tapan District are the extended family, namely Ndoang, Unyai, Con, Cung, Mak Dih, Jatan, Gadih, Manatung, Cucuang, Piyut.